Modèles de dangerosité : les contrevenants sexuels et la loi - Petrunik, Michael (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1994)
The history of dangerous offender legislation reveals a selective focus on few sexual and violent offenders many of whom are not demonstrably more dangerous than most of the offenders from the larger pool of sexual and violent offenders from which they are drawn. To the extent such legislation draws attention from routine frequently occuring forms of violence in favour of the violence of a few predatory offenders it is clearly problematic. Nonetheless, there are good reasons such legislation is likely to be retained and perhaps modified to place a greater emphasis on community protection.